Amygdaloid kindled seizures can induce functional and pathological changes in thymus of rat: Role of the sympathetic nervous system - Rekha Bhatt; Suresh Bhatt; Meera Hameed; Pranela Rameshwar; Allan Siegel (Neurobiology of Disease, 2006)
The present study sought to determine the effects of long-term kindled seizures of the basal amygdala upon immune function in rat, utilizing the thymus, as a principal target for study. Histopathology from kindled Sprague–Dawley rats revealed the presence of epithelial cell thymoma in 70% of these rats. The results revealed an increased rate of apoptosis and proliferation in thymic epithelial cells. Analysis of thymocytes indicated a decrease in the ratio of CD4 to CD8 positive T cells and reduced proliferative response to T-cell mitogens. To determine whether these effects were mediated through the sympathetic nervous system, animals were treated with guanethidine, which blocked the development of epithelial cell thymomas, while mifepristone treatment, employed to determine the possible role of the hypothalamic–pituitary axis, was ineffective in attenuating thymoma development. Thus, the present study demonstrated that functional and pathological changes in the thymus during kindled seizures are mediated through the sympathetic nervous system.